Benin : Poverty Reduction Strategy Paper-Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2005)
The Joint Staff Advisory Note (JSAN) of the Poverty Reduction Strategy Paper Annual Progress Report on Benin highlights the progress in implementing the strategy. As evaluated by Benin's first annual progress report (APR), the PRS remains a sound strategy for poverty reduction in Benin. The authorities intend to shorten the preparation time of the APR and to achieve a closer integration of the PRS monitoring and evaluation process with the policy cycle. The APR process has been an effective instrument for improving donors' coordination and harmonization.